PEMBELAJARAN PEMAHAMAN MENGENAI DIAGRAM BATANG PADA SISWA SD KELAS IV MELALUI MODEL PROJECT BASED LEARNING - Fauzi Rochman; Jajang Bayu Kelana (COLLASE (Creative of Learning Students Elementary Education), 2022)
This research is motivated by the importance of statistical materials, especially bar charts, which are studied in grade 4 SD in everyday life and as a provision for the ability to face the 21st century. This study aims to describe the learning of the 4th-grade students' understanding of bar charts using the Project-Based Learning (PjBL) model. The research method used in this research is a descriptive qualitative method. The sample of this study was grade 4 students of SD Mutiara Bunda, totaling 24 people. The research instruments used in this study were questions, questionnaires, observation sheets, and interview results. Data analysis was carried out quantitatively to determine students' understanding of the bar chart after going through the learning process using the PjBL model. Analyze questionnaires, observation sheets, and interview results to determine the responses of teachers and students and the implementation of PjBL in bar chart learning. Based on the research results obtained: students' understanding of the bar chart using the PjBL model is in a good category and the response and implementation of the PjBL model to understand this bar chart are in a very good category.